2014
DOI: 10.1007/s12035-014-8826-2
|View full text |Cite
|
Sign up to set email alerts
|

Updated Findings of the Association and Functional Studies of DRD2/ANKK1 Variants with Addictions

Abstract: Both nicotine and alcohol addictions are severe public health hazards worldwide. Various twin and family studies have demonstrated that genetic factors contribute to vulnerability to these addictions; however, the susceptibility genes and the variants underlying them remain largely unknown. Of susceptibility genes investigated for addictions, DRD2 has received much attention. Considering new evidence supporting the association of DRD2 and its adjacent gene ankyrin repeat and kinase domain containing 1 (ANKK1) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 193 publications
0
22
0
1
Order By: Relevance
“…Further, functional magnetic resonance imaging (fMRI) studies on healthy subjects without any diagnosed mental disorders demonstrated that A9 homozygote or heterozygote carriers had a greater brain ventral striatal response to both anticipation and receipt of reward than that of A10 homozygote carriers (Dreher et al, 2009, Forbes et al, 2009). In addition, several meta-analyses, including the one recently reported by our group, have shown that the SLC6A3 VNTR is significantly associated with smoking cessation (Ma et al, 2015b) and various psychiatric disorders (Yang et al, 2007, Kambeitz et al, 2014), which are all correlated with AD (Ma et al, 2014, Li and Burmeister, 2009). Therefore, it is plausible to infer that the VNTR genotypes confer susceptibility to alcoholism.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Further, functional magnetic resonance imaging (fMRI) studies on healthy subjects without any diagnosed mental disorders demonstrated that A9 homozygote or heterozygote carriers had a greater brain ventral striatal response to both anticipation and receipt of reward than that of A10 homozygote carriers (Dreher et al, 2009, Forbes et al, 2009). In addition, several meta-analyses, including the one recently reported by our group, have shown that the SLC6A3 VNTR is significantly associated with smoking cessation (Ma et al, 2015b) and various psychiatric disorders (Yang et al, 2007, Kambeitz et al, 2014), which are all correlated with AD (Ma et al, 2014, Li and Burmeister, 2009). Therefore, it is plausible to infer that the VNTR genotypes confer susceptibility to alcoholism.…”
Section: Introductionmentioning
confidence: 88%
“…Particularly, the dopaminergic mesocorticolimbic reward pathways have been linked to the pathogenesis of addictions, including alcoholism. Consequently, genes with a dopaminergic function have received much attention in relation to the etiology of AD and other addictions (Muramatsu and Higuchi, 1995, van der Zwaluw et al, 2009, Ma et al, 2014, Ma et al, 2015a). …”
Section: Introductionmentioning
confidence: 99%
“…One of the most important system intervening reward mechanisms is considered to be dopaminergic pathways. Dopaminergic neurons are present in VTA of midbrain, projected into nucleus accumbens and ventral striatum [1] All the genes, involved in regulating the assembly of this system in brain is of great interest and can be a suitable candidate for investigation of molecular basis of addiction and several other psychiatric disorders [2]. Among these, the gene of interest that effect the dopaminergic neurotransmission is the Dopamine D2 receptor (DRD2) gene that is located at chromosome 11q22-23 encoding a G-Protein coupled receptor (Giinhibitory G protein) in post synaptic neurons [3] performing dual function of inhibitory auto receptor and a post synaptic receptors [4].…”
Section: Introductionmentioning
confidence: 99%
“…This is because the SNP rs1800497 was previously believed to be located within the dopamine D 2 receptor gene ( DRD2 ), but is actually located in the adjacent ANKK1 gene. Although loci across several genes in this region ( NCAM1-TTC12-ANKK1-DRD2 ) are in high linkage disequilibrium (LD) (i.e., non-random associations among alleles; Mota et al 2012), this particular locus has been of focus due frequent association with addictive phenotypes and its putative role in the dopaminergic system (Ma et al 2015). Furthermore, positron emission tomography has revealed that rs1800497 is related to dopamine D 2 /D 3 receptor density (Thompson et al 1997; Pohjalainen et al 1998; Jönsson et al 1999; Savitz et al 2013).…”
Section: Introductionmentioning
confidence: 99%